Print Advertisements Used by Tourism Department of Yogyakarta Government: Multimodality Discourse Analysis - Saputri, Cahyani Adelia (Language Horizon: Journal of Language Studies, 2023)
Advertising in the tourism industry has an important role in promoting tourist destinations. The tourism print advertising component is very important to build meaning and attract readers to visit tourist attractions. Thus, the analysis of tourism print advertisements is very important to create good meaning through the meaning of the representation and the role of the print advertisement. The main objects of this research are three printed tourism advertisement brochures used by the Tourism Department of Yogyakarta Government. This study uses qualitative methods to analyze data. The research data was collected using documentation, interviews, and questionnaires. This study reveals the meaning of semiotic representations in three brochures where the deeper relationship between tourism advertisement objects in advertisements is beyond definition. The role of print advertising in promoting tourist attractions to attract visitors shows success through print advertisements owned by the Tourism Department of Yogyakarta Government that are appropriate and fulfill the advertising function. This study will be very good if further studies can find more in-depth topics to be discussed or other topics to conduct multimodal discourse analysis, especially on tourism advertising. Keywords: multimodal, tourism, brochures, advertising, narrative, conceptual.